Growing Pains: About ChatGPT and Other Chatbots. - Xinzhen, Lan (Beijing Review, 2023)
In the short time since ChatGPT's launch, China's efforts to regulate GAI convey its support for the new technology. The Chinese Cyberspace Administration issued a draft policy on the management of generative artificial intelligence (GAI) services on April 11, soliciting suggestions and advice from the public. As the draft policy has pointed out, China supports the application of as well as international cooperation on innovative technologies such as AI.